Comparative Analysis of the Level of Financial Efficiency in the National Construction Services Industry Before and After the Implementation of PSAK 72 with a Two-Stage Data Envelopment Analysis Approach - Muhammad Aulia Andriyono; Trinandari Prasetyo Nugrahanti (West Science Accounting and Finance, 2024)
This study analyzes the financial efficiency of Indonesia's national construction services industry before and after the implementation of PSAK 72 using the Data Envelopment Analysis (DEA) method. It aims to address the poor performance of contractor companies, which have negative operating cash flows and high Debt to Equity Ratios (DER). Input variables include Net Fixed Assets, Operating Expenses, and Total Employees, while output variables are Revenue and Profit Before Tax. Efficiency scores range from 0 to 1, with scores close to 1 indicating high efficiency. Prior to PSAK 72, PP Presisi Tbk and Wijaya Karya Bangunan Gedung Tbk were the most efficient companies, consistently achieving perfect efficiency scores. Total Bangun Persada Tbk was the least efficient. After PSAK 72, Bukaka Teknik Utama Tbk reached maximum efficiency in 2021, while Brantas Abipraya (Persero) was the least efficient in 2020. A Kolmogorov-Smirnov normality test showed the data was not normally distributed, leading to a non-parametric Wilcoxon signed rank test. The test indicated a significant difference in financial efficiency before and after PSAK 72, with a p-value of 0.04. This suggests a notable impact of PSAK 72 on the efficiency of construction companies.